Nature-inspired rollable electronics - Lee, Gunhee; Choi, Yong Whan; Lee, Taemin; Lim, Kyung Seob; Shin, Jooyeon; Kim, Taewi; Kim, Hyun Kuk; Koo, Bon Kwon; Kim, Han Byul; Lee, Jong Gu; Ahn, Kihyeon; Lee, Eunhan; et al. (NPG Asia Materials, 2019)
Inspired by the rolling mechanism of the proboscis of a butterfly, rollable electronics that can be rolled and unrolled to a great extent on demand are developed. Generally, electronic devices that are attached to various surfaces to acquire biosignals require mechanical flexibility and sufficient adhesive force. The rollable platform provides sufficient force that grips onto the entire target surface without destroying the target organ. To prove the versatility of our device not only in gripping and detecting biosignals from micro objects but also in performing a variety of functions, thin-film electronics including a heater, strain sensor and temperature sensor are constructed on the rollable platform, and it is confirmed that all the electronics operate normally in the rolled and unrolled states without breakdown. Then, micro bio-objects are gripped by using the rollable platform, and their tiny motions are successfully detected with the sensor on the platform. Furthermore, the detection of the pulse wave signals of swine under diverse experimental conditions is successfully conducted by rolling up the rollable system around the blood vessel of the swine, the result of which proves the feasibility of a rollable platform as a biomedical device.
Keywords: Biomedical devices; Electronic device; Experimental conditions; Mechanical flexibility; Pulse wave signal; Rolling mechanism; Target surface; Thin film electronics